2013
DOI: 10.1902/jop.2012.110674
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Recombinant Human Bone Morphogenetic Protein 2 Associated With a Variety of Bone Substitutes on Vertical Guided Bone Regeneration in Rabbit Calvarium

Abstract: The use of rhBMP-2/absorbable collagen sponge (ACS) combined with all of the bone substitute materials tested resulted in a greater amount of bone formation than that produced with the bone substitute materials alone or rhBMP-2/(ACS) and CL using the rabbit calvarium GBR model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
35
1
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(44 citation statements)
references
References 50 publications
(189 reference statements)
4
35
1
4
Order By: Relevance
“…In the present study, CPP with Ca/P ratio of 1 was compared with BCP with Ca/P ratio of 1.55, the most common graft material in clinical practice. In recent years, numerous studies have incorporated growth factors, such as, rhBMP-2, with various bone graft biomaterials to enhance bone regeneration [24]. The bone regeneration capacity of rhBMP-2 is dependent on carrier type [36,37], and a good carrier should load protein easily, secure a space for regeneration, and exhibit bioabsorbable and bioactive degradation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the present study, CPP with Ca/P ratio of 1 was compared with BCP with Ca/P ratio of 1.55, the most common graft material in clinical practice. In recent years, numerous studies have incorporated growth factors, such as, rhBMP-2, with various bone graft biomaterials to enhance bone regeneration [24]. The bone regeneration capacity of rhBMP-2 is dependent on carrier type [36,37], and a good carrier should load protein easily, secure a space for regeneration, and exhibit bioabsorbable and bioactive degradation.…”
Section: Discussionmentioning
confidence: 99%
“…The use of synthetic bone in clinical practice is limited by lack of osteoinductivity [24]. Osteoinductive proteins, such as recombinant human bone morphogenetic protein-2 (rhBMP-2), promote the differentiation of mesenchymal stem cells (MSCs) and pre-osteoblast into osteoblasts and trigger the migration of osteoblasts [25,26].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The goal of regenerative periodontal surgery is to predictably restore the tooth's supporting apparatus (i.e., root cementum, periodontal ligament [PDL], and bone), which have been lost following periodontal disease or trauma 1‐3 . Various bone grafts, including autogenous bone, allografts, xenografts, and synthetic alloplasts, have been used with varying degrees of success for the treatment of bone and periodontal defects 4‐12 . One grafting material that has been particularly effective because of its combination of osteoconduction and osteo‐induction is demineralized freeze‐dried bone allograft (DFDBA) 13‐17 .…”
mentioning
confidence: 99%
“…In animal models or clinical trials, BMPs were applied in combination with various carrier systems for the purpose of bone regeneration in the procedures of socket grafting, 16 , 19 sinus grafting, 20 , 21 periodontal repair, 22 localized bone augmentation, 17 , 23 and implant osseointegration 16 , 24 . Previous literature has shown that recombinant human bone morphogenetic protein (rhBMP)‐2 could not only promote osseointegration, but also induce new bone formation in VBA 25 , 26 …”
mentioning
confidence: 99%